Performance analysis of scale-free communities in ad hoc networks - Filiposka, Sonja; Trajanov, Dimitar; Grnarov, Aksenti (IEEE, 2009)
The underlying user’s social network plays the most significant part in the distribution of the end-to-end traffic in the ad hoc network. In this paper we propose a new model for a user social network based on the scale-free phenomenon and smallworld clustering effect that can be found in the real social networks. The proposed model is then used for creation of new traffic and physical movement models in order to investigate the performances of the ad hoc network. The results point out that the expected network performances can be much higher than the ones evaluated using simple random movement and traffic generators.
Keywords: ad hoc networks, communities, performances, scale free and small world phenomena